Analisis Pengetahuan dan Sikap Ibu Hamil dalam Mengkonsumsi Tablet Fe - Antri Ariani; Lulu Amirah; Andria Pragholapati (Jurnal Kebidanan Harapan Ibu Pekalongan, 2022)
The need for iron during pregnancy increases, this increase is increased to meet the needs of the fetus to grow. Obtained pregnant women with fe coverage of 35.44% in Sukawarna health center. Interview with 10 pregnant women where the condition after consuming Fe tablets is that women feel nauseous because of the nausea effects there are some pregnant women who do not take Fe tablets. The purpose of this study was to determine the description of knowledge, attitudes and characteristics of pregnant women in the importance of consuming Fe tablets at the Sukawarna Community Health Center in Bandung in 2019. This study aims to determine the description of knowledge, attitudes of pregnant women in the importance of consuming iron tablets in Puskesmas Sukawarna. The design used is descriptive research. With data obtained through questionnaire data collection from pregnant women. Data is presented in the form of frequency distribution with univariate analysis. With a population of 130 people, and a total sample of 56 people with accidental sampling technique. The results showed that almost all respondents had good knowledge and in terms of attitude showed that more than half of respondents did not support. It is expected that pregnant women will be more aware of the importance of consuming iron tablets during pregnancy in order to prevent anemia in pregnancy, especially to health workers to further improve IEC on supplementing FE tablets and cooperation between health workers in the form and family to form a supportive attitude. The conclusions in this study parity, socioeconomic, knowledge and sikap mother affects mothers in ANC visit. Therefore health workers to provide counseling to pregnant women about the importance of antenatal care through public lectures and interviews with clients, by communicating health messages are organized by the department of health through health centers.